A Comparative Analysis of Home Advantage in the Olympic and Paralympic Games 1988–2018. Issue 2 (3rd April 2021) - Wilson, Darryl; Ramchandani, Girish
Abstract: In this paper we examine the extent to which nations that are awarded the right to host the Olympic and Paralympic Games benefit from success in elite sport through a quantifiable home advantage or host nation effect. The prevalence and size of home advantage in the Olympic and Paralympic Games is investigated over 16 editions (eight Summer Games and eight Winter Games) between 1988 and 2018 at an overall nation level and within ten sports. These include seven summer sports (archery, athletics, cycling, fencing, shooting, swimming and table tennis) and three winter sports (alpine skiing, biathlon and cross-country skiing). Our study supports the prevalence of a statistically significant overall host nation effect in the Olympic and Paralympic Games, which is also evident in Olympic archery, Paralympic athletics, Paralympic table tennis and Paralympic alpine skiing. At the same time, our analysis illustrates that the size of this effect did not differ significantly between able-bodied and para-sport events. Nations that experienced a large home advantage effect in the Olympic Games also had a large home advantage effect in the Paralympic Games. Our research contributes to the study of the impacts of hosting international multi-sport competitions, including the largely overlooked area of the Paralympic Games.